Slovenščina kot dediščinski jezik v slovenski skupnosti v Torontu - Kralj, Tadej (Jezik in slovstvo, 2020)
The Slovenian community in multicultural Toronto functions with two official languages: English and French. In my contribution, I place Slovenian among heritage languages brought by speakers from their authentic environment - in this case, the Slovenian-speaking environment - on immigrating and transmitted to the next generations of the Slovenian immigrants' descendants. I deal with a position of Slovenian as a heritage language in the Slovenian community. I am interested in the role of Slovenian with three types of language users identified with a help of heritage language theory.
Keywords: dediščinski jezik; heritage language; language user; Slovenian community; Slovenian language; slovenska skupnost; slovenščina; Toronto; uporabnik jezika